Maternal vitamin D status during pregnancy and child outcomes. - Gale, C; Robinson, S; Harvey, N; Javaid, M; Jiang, B; Martyn, C; Godfrey, K; Cooper, C (2008)
OBJECTIVE: To investigate whether exposure to high maternal concentrations of 25(OH)-vitamin D in pregnancy poses any risk to the child. DESIGN: Prospective study. SETTING: Princess Anne Maternity Hospital, Southampton, UK. SUBJECTS: A group of 596 pregnant women were recruited. A total of 466 (78%) children were examined at birth, 440 (74%) at age 9 months and 178 (30%) at age 9 years. METHODS: Maternal 25 (OH)-vitamin D concentrations were measured in late pregnancy. Anthropometry of the child was recorded at birth, 9 months and 9 years. At 9 months, atopic eczema was assessed. At 9 years, children had an echocardiogram and a dual energy x-ray absorptiometry scan, blood pressure, arterial compliance and carotid intima-media thickness were measured and intelligence and psychological function assessed. RESULTS: There were no associations between maternal 25(OH)-vitamin D concentrations and the child's body size or measures of the child's intelligence, psychological health or cardiovascular system. Children whose mothers had a 25(OH)-vitamin D concentration in pregnancy >75 nmol/l had an increased risk of eczema on examination at 9 months (OR 3.26, 95% CI 1.15-9.29, P=0.025) and asthma at age 9 years (OR 5.40, 95% CI, 1.09-26.65, P=0.038) compared to children whose mothers had a concentration of <30 nmol/l. CONCLUSION: Exposure to maternal concentrations of 25(OH)-vitamin D in pregnancy in excess of 75 nmol/l does not appear to influence the child's intelligence, psychological health or cardiovascular system; there could be an increased risk of atopic disorders, but this needs confirmation in other studies.